2011
DOI: 10.1002/hep.24094
|View full text |Cite
|
Sign up to set email alerts
|

Identifying who is at risk of drug-induced liver injury: Is human leukocyte antigen specificity the key?

Abstract: In the classical form of alpha1-antitrypsin (AT) deficiency, a point mutation in AT alters the folding of a liver-derived secretory glycoprotein and renders it aggregation-prone. In addition to decreased serum concentrations of AT, the disorder is characterized by accumulation of the mutant alpha1-antitrypsin Z (ATZ) variant inside cells, causing hepatic fibrosis and/or carcinogenesis by a gain-of-toxic function mechanism. The proteasomal and autophagic pathways are known to mediate degradation of ATZ. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Interestingly, HLA variants have been linked to autoimmune hepatitis (7, 11, 12). Association of HLA variants has been described with different drugs as amoxicilin-clavulanate (16, 17), flucoxacilin (11), ximelagatran (11), lapatinib (18), lumiracoxib (19, 20), and neviparine (21). Sharma et al showed a fourfold increased risk of ATDH in patients without HLADQA1*0102 haplotype suggesting to play a role in pathogenic development of ATDH (12).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HLA variants have been linked to autoimmune hepatitis (7, 11, 12). Association of HLA variants has been described with different drugs as amoxicilin-clavulanate (16, 17), flucoxacilin (11), ximelagatran (11), lapatinib (18), lumiracoxib (19, 20), and neviparine (21). Sharma et al showed a fourfold increased risk of ATDH in patients without HLADQA1*0102 haplotype suggesting to play a role in pathogenic development of ATDH (12).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, patients were selected by ALT and/or AST ≥ 3ULN under lumiracoxib and compared to a lumiracoxib-treated control group without liver enzyme elevations. The clinical relevance of such findings may be limited since, in contrast to the flucloxacillin study, most patients exhibiting this polymorphism were asymptomatic [26] . Thus, differentiation may be difficult between frequent asymptomatic elevations of liver enzymes and rare but severe DILI.…”
Section: Impact Of Positive Identification Of Dili Patients and The Cmentioning
confidence: 91%
“…Other medications such as ximelagatran, an anticoagulant which was voluntarily withdrawn from the global market by AstraZeneca in 2006, exhibit immunemediated hepatotoxicity that may be predisposed by allelic variants in the HLA major histocompatibility complex (MHC) class II region, providing a platform to recapitulate known genomic associations [39]. Similarly, research has found that lumiracoxib, removed from the Australian market in 2007, has a strong association between the hepatotoxicity and HLA alleles within the MHC class II region, for example, DQA*0102, inferring that these HLA alleles have higher sensitivity in the identified 41 cases of lumiracoxib-induced liver injury compared to control lumiracoxib-exposed liver tissue [40,41]. These examples highlight why it is critical to include immune cells and other parenchyma cellsl/NPC in a microphysiological model to effectively investigate the interaction of the immune-mediated and non-immune-mediated mechanisms of iDILI.…”
Section: Immune-mediated Mechanismmentioning
confidence: 99%